Neo-Thomistic Criticism of Kant’s Ethics in Lithuania - Burnys, Z. (Problemos, 1979)
The article attempts to draw a parallel between Kant’s ethics and religion by way of analysis of the contents of the categories of virtue, happiness, duty, faith, righteousness, sacredness, highest bliss and others. Neo-Thomist criticism of Kant’s ethics is given in terms of Marxist methodology. It is found in conclusion that the neo-Thomists of bourgeois Lithuania could not give an adequate appreciation of Kant's ethics. It is found in conclusion that, their motives being essentially religious rather than scholarly, the neo-Thomists of bourgeois Lithuania could not give an adequate appreciation of Kant’s ethics.